Solvent issues during processing and device lifetime for perovskite solar cells - Peter Holliman (Materials Research Innovations, 2015)
This paper considers the manufacturing issues associated with dimethyl formamide, γ-butyrolactone, dimethyl sulfoxide and chlorobenzene solvents, in particular the health and safety issues of using these solvents in scaled perovskite photovoltaic processing. Issues of device lifetime are also considered, for example the effects of atmospheric conditions (e.g. humidity).